The Role of Islamic Religious Education Teachers in Shaping Students’ Noble Character (Akhlakul Karimah) - Raihani Aththahirah; Rosdialena R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic Religious Education plays an important role in shaping the noble character of students as a provision in both personal and social life. The development of technology and increasingly complex social changes demand the strengthening of character education in the school environment, so Islamic Religious Education teachers are required to be able to carry out their roles optimally in fostering the character of students. This study aims to examine the role of Islamic Religious Education teachers in shaping the noble character of students. This study uses a qualitative approach with a library research type, by reviewing various scientific literature in the form of books, journals, articles, and other documents related to the role of teachers and character development in the Islamic perspective. The data is analyzed using qualitative descriptive techniques to obtain a comprehensive picture of the strategies used by teachers in shaping students' character. The results of the study show that Islamic Education teachers act as mentors, role models, motivators, as well as evaluators in the process of moral development through exemplification, habituation, advice, and instilling Islamic values in learning. Therefore, the success of shaping students' noble character is greatly influenced by the teachers' earnestness in consistently integrating Islamic values within the educational environment.